AGENDA SETTING PENGELOLAAN SAMPAH PLASTIK DI KOTA PALU - Putri, Nanda Asri Aqiqah; Riadi, Slamet; Firmansyah, Andi Maman (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to analyze and determine what actions were taken by the Environmental Service in the process of formulating Palu City Mayor Regulation Number 40 of 2021. The research method is a qualitative research method. The location of this research is at the Environmental Service. In this study, the analysis used is the Cobb and Elder theory which states 5 Agenda Setting concepts including Private Problems, Public Problems, Political Issues, Systemic Agendas, and Institutional Agendas. There were 2 informants in this study. The conclusion of this study is that research on waste management in Palu City shows that this problem has transformed from a personal issue to an urgent public issue. The increase in the amount of waste after a natural disaster requires the government to take more serious action. Active community participation through education programs and waste management has been the key to success in overcoming this problem. Although the policies that have been implemented show progress, challenges in the consistency of implementation and public understanding still need to be considered. With a systematic and collaborative approach, it is expected that waste management in Palu City can be more effective and sustainable.